2021
DOI: 10.1371/journal.pone.0245535
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the dynamics of obesity prevention policy decision-making using a systems perspective: A case study of Healthy Together Victoria

Abstract: Introduction Despite global recommendations for governments to implement a comprehensive suite of policies to address obesity, policy adoption has been deficient globally. This paper utilised political science theory and systems thinking methods to examine the dynamics underlying decisions regarding obesity prevention policy adoption within the context of the Australian state government initiative, Healthy Together Victoria (HTV) (2011–2016). The aim was to understand key influences on policy processes, and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 80 publications
0
56
0
1
Order By: Relevance
“…In terms of research aims found in the 23 articles, four themes emerged: 1) to examine the complexity of a public health topic and illustrate complex systems thinking [26][27][28][29][30][31][32][33][34]; 2) to discuss the complexity of a public health intervention [35][36][37][38][39][40]; 3) to describe study protocol and how CLDs were created [41][42][43][44]; and 4) to illustrate how CLDs can be used to monitor and track initiatives to improve population health or evaluate impact of interventions [45][46][47][48].…”
Section: Research Aimsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of research aims found in the 23 articles, four themes emerged: 1) to examine the complexity of a public health topic and illustrate complex systems thinking [26][27][28][29][30][31][32][33][34]; 2) to discuss the complexity of a public health intervention [35][36][37][38][39][40]; 3) to describe study protocol and how CLDs were created [41][42][43][44]; and 4) to illustrate how CLDs can be used to monitor and track initiatives to improve population health or evaluate impact of interventions [45][46][47][48].…”
Section: Research Aimsmentioning
confidence: 99%
“…Both primary and secondary data were used for creating CLDs (Table 3). Most articles reported on primary data collection (18/ 23) and this included interviews [26,27,33,[35][36][37][38][39][40], group model building with stakeholders and/or community members [32,41,43,44,46,48], behavioral data [42,47], fieldnotes [37], and workshops with experts [31]. Twelve articles used primary data only.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Systems thinking for prevention requires significant expertise to map systems and locate leverage points to alter their behaviour [29]. At macro and micro levels systems practice requires the reflecting, learning and adapting cycles of emergent strategy to facilitate system interactions via convening stakeholders, engaging communities, connecting agencies, coordinating assets, testing interventions, building consensus and aligning activities [30][31][32]. It involves taking risks in dynamic environments and continuously learning from them to prevent obesity, family violence, diabetes and other chronic problems [33].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Critical for implementing policy changes is the meaningful involvement of government actors, as well as the consideration of the characteristics, barriers, and facilitators of the political decision‐making process. For instance, investigating the dynamics of obesity prevention policy decision‐making of the Healthy Together Victoria initiative (a state government‐led, multi‐level, multi‐setting complex systems approach to obesity prevention in Australia), Clarke et al 30 identified that alignment of policy proposals to other government objectives and development of viable policy solutions that met the requirements and beliefs of decision‐makers were important facilitators for policy adoption. In contrast, the organizational culture of risk aversion and time required for the policy process can create barriers and delays in the policy decision‐making process.…”
Section: An Action‐oriented Framework For Systems Changes For Childhood Obesity Preventionmentioning
confidence: 99%